Four MES genes from calamondin (Citrofortunella microcarpa) regulated citrus bacterial canker resistance through the plant hormone pathway - Xiao, Yu-Xiong; Xiao, Cui; Tong, Zhu; He, Xiu-Juan; Wang, Ze-Qiong; Zhang, Hai-Yue; Qiu, Wen-Ming (Frontiers in Plant Science, 2025)
Citrus bacterial canker (CBC) disease, caused by Xanthomonas citri subsp. citri (Xcc), is one of the major diseases that seriously endanger citrus production. Citrus regulates the balance of endogenous plant hormones to resist CBC through multiple synthetic pathways, including the demethylation pathways of methyl salicylate (MeSA), methyl jasmonate (MeJA) and methyl indole-3-acetic acid (MeIAA). Here, four methylesterase (MES) genes, MES1.1, MES17.3, MES10.2, and MES1.5 were screened in the transcriptomes of CBC-resistant and CBC-susceptible varieties after Xcc inoculation. Among these MES genes, the expression levels of MES10.2, MES1.1, and MES1.5 were up-regulated in CBC-resistant varieties, while MES17.3 was down-regulated in both CBC-resistant and susceptible varieties. Subcellular localization analysis showed that the four MES-encoding proteins were localized in the cytoplasm. Overexpression of CmMES1.1 and CmMES1.5 from calamondin (Citrofortunella microcarpa) significantly enhanced CBC resistance and increased the salicylic acid (SA) content in calamondin. Conversely, overexpression of CmMES10.2 and CmMES17.3 significantly reduced CBC resistance and increased the contents of jasmonic acid (JA) and indole-3-acetic acid (IAA), respectively. We concluded that the resistant varieties confer CBC-resistance by regulating the expression of CmMES1.1 and CmMES1.5 to increase SA content, and regulating CmMES10.2 and CmMES17.3 to inhibit the synthesis of JA and IAA, respectively. Their ability to regulate the endogenous SA, JA and IAA content through the demethylation pathway was an attractive breeding target for conferring CBC resistance.